Achieving academic promotion - Mahat, Marian; Tatebe, Jennifer (Surviving and thriving in academia, 2019)
This book demystifies the academic promotion process by bringing together international perspectives - both personal accounts and reflections on the structures and processes of promotion in different contexts - to help you understand the steps you can take at any stage of your career to move up the ladder.